If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 3x + -1 = 33 Reorder the terms: -1 + X + 3x = 33 Solving -1 + X + 3x = 33 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + X + 1 + 3x = 33 + 1 Reorder the terms: -1 + 1 + X + 3x = 33 + 1 Combine like terms: -1 + 1 = 0 0 + X + 3x = 33 + 1 X + 3x = 33 + 1 Combine like terms: 33 + 1 = 34 X + 3x = 34 Add '-3x' to each side of the equation. X + 3x + -3x = 34 + -3x Combine like terms: 3x + -3x = 0 X + 0 = 34 + -3x X = 34 + -3x Simplifying X = 34 + -3x
| 16+7c=51 | | x^2+.12x-.054=0 | | 2w=2.56 | | -28+p=(p-10) | | -26/50 | | 22x-3.5=18.5 | | y+6(y-9)= | | y=41x-(88000+33x) | | 7x+6x+3+8=10x+5+2x | | 13x+.64x=100 | | 6x-14-4x=6x-9 | | (4X+7)+(2X-16)= | | 7(4y-9)-(2y+6)= | | 3y-10=x | | u=5(8n+35)+6(n+1) | | 5n+9=3n-1 | | (4c^8d^-6)/8d^3)^-1 | | (4X+7)+(2-16)= | | 5m=18+2m | | log(9x)=1 | | (2+y)(2y+3)=0 | | x=-14+3(4) | | (-4.5)+4.9+3.4= | | 18+10=m | | 2.5x-3(x+1)=12 | | 4x^9n+4=256 | | -70+15y+2y=-2 | | 3/9y-5=-2 | | h=15-8 | | (-5)+(-7.1)= | | 8=-9x+3 | | 4x(5x+3)=2x(7x+6) |